Attitude of Muslim consumers towards sex appeal in advertising: A comparative study between sub-cultures in Malaysia - Ismail, A.R.; Melewar, T. (Routledge, 2014)
This research was designed in order to explore the subculture differences in Malaysian consumers’ responses to sex appeal advertising. This study employs a 2 × 2 × 2 full factorial between subjects design. There are two levels of model gender (male/female), two levels of sex appeal (high/low), and two levels of religion of the subjects (Muslim/non-Muslim). When comparing Muslims and non-Muslims in the responses to the ads, it was generally found that Muslim subjects’ attitudes were significantly lower than non-Muslims attitudes toward the same ads. Future research should adopt a more representative sample and test different product categories.